Revising the flaws of the digital signature act 1997 in governing security of electronic transactions / Hartini Saripan and Zaiton Hamin - Saripan, Hartini; Hamin, Zaiton (Research Management Institute, 2011)
Notwithstanding the fact that Malaysia is one of the first countries to have the digital signature legislation, the current digital signature laws are flawed, which suggest their inability to secure electronic transactions. A considerable amount of literature has been published on this matter and these studies have shown numerous criticisms on the shortcomings of the Digital Signature Act 1997 (hereinafter the 1997 Act) and its Regulations 1998 (hereinafter the 1998 Regulations). In this regard, there has been a consensus in the literature for the past ten years that this Act is incomplete and has failed to recognize the fast changing pace of modern technologies. This project aims to focus on the instrumental and the normative drawbacks of the Malaysian digital signature laws and propose some recommendations to address such flaws. Whilst the laws were created more than thirteen years ago, recommendations based on more advanced theoretical and conceptual frameworks, which are relevant in governing security of electronic transactions, are urgently needed in order to facilitate a far-reaching environment of paperless communications. Adopting a purely doctrinal legal research methodology, the project will triangulate the primary sources obtained from the relevant statutes including the 1997 Act and the 1998 Regulations, hansard as well as a body of case law with the secondary sources such as journal articles, books and other written commentaries on the case law and legislation.